"Spirit in man, art and literature/by Carl Gustav Jung;translated by R. F. C. Hull" - "Jung, Carl Gustav" (London, 2003)
This book explain Some of Jung's best insights into artistic and literary creation. Essays on Freud, Wilhelm, Picasso, Joyce, and on poetry and literature.
Keywords: Psychology